Senegal : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criteria and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2004)
The First Review Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criteria for Senegal are discussed. Economic activity in the first half of 2003 has been weaker than envisaged under the program. The impact of softer domestic demand, reflecting mainly the drop in rural incomes in 2002 and a low pace of public spending in the first six months of the year, has been compounded by a slowdown in the mining and chemical sectors.